Exploring the adoption and utilisation of ChatGPT in everyday academic practices among medical and dental students of Rawalpindi and Islamabad: a study on the impact and perceived effectiveness - Khadija Qamar; Saad Waseem Butt; Mehwish Abaid; Ahmed Rashid; Rafia Tahira; Aarij Sohail Iqbal (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the usage of chatbot generative pretrained transformer among medical and dental students in Pakistan. Method: The cross-sectional study was conducted at the Army Medical College, National University of Medical Sciences, Islamabad, Pakistan, from June 15 to July 31, 2023, and comprised medical and dental students in public and private medical and dental colleges of Rawalpindi and Islamabad who had used the chatbot generative pretrained transformer programme at least once for their academics or had prior knowledge of it. Responses were obtained through a structured online survey. Data was analysed using SPSS 27. Result: Of the 315 respondents, 181(57.5%) were females, 134(42.5%) were males, 260(82.5%) were from public institutions, 55(17.5%) were from private, 259(82.20%) were medical students and 56(17.80%) were dental students. Overall, 192(61%) respondents had used ChatGPT for academics prior to the study. For them, its utility was most for case-based learning, problem-based learning and for seeking clarification of topics. Fruitful acquisition of knowledge was reported by 85.7% of the study participants and 72.8% participants regarded ChatGPT as a valuable resource for improving academic performance. The mean perceived usefulness score was 17.93±5.08 and the mean perceived risk score was 8.46±2.44. Conclusion: Chatbot generative pretrained transformer was found to improve academic performance of medical and dental students. Key Words: Academic performance, Medical education, Problem-based learning, Research, Risk.